The lived experience of living liver donors: A meta-synthesis of qualitative studies - Dong, Li; Li, Zhiru; Lv, Feicui; Zheng, Li; Lu, Fangyan (BMC nursing, 2024)
Living liver donors are frequently used for liver transplantation, but they experience many physical changes and psychological challenges. A better understanding of the experiences of liver donors can provide them with comprehensive and individualized patient-centred support and health care. Thus, this study sought to identify and synthesize existing qualitative studies to develop an in-depth understanding of the lived experiences of living liver donors. A meta-synthesis was conducted and reported in accordance with the Enhancing Transparency in Reporting the Synthesis of Qualitative Research statement. Seven databases were systematically searched from inception to March, 2024, using a combination of Medical Subject Headings with keywords. The results were integrated using the three-step thematic synthesis method suggested by Thomas and Harden. Nine studies met the inclusion criteria and were included in this meta-synthesis. Four themes emerged from the meta-synthesis: (1) facing a life-changing situation, (2) experiencing changes in interpersonal relationships, (3) coping with changes, and (4) achieving personal growth. Living liver donors experienced physical, psychological, and social changes after surgery, striving to manage these challenges, highlighting the importance of coping strategies and ultimately achieving personal growth. Future nursing research should focus on psychological interventions, supportive measures, and the positive aspects of living liver donors to help them achieve the optimal quality of life. PROSPERO CRD42022328947.